Die aard van pleegvaders se betrokkenheid by pleegkinders : ‘n verkennende studie binneChild Welfare Tshwane - Le Roux, M.P. (Liana) (University of Pretoria, 2014)
Dissertation (MSW)--University of Pretoria, 2013.